Effect of bacterial toxin identified from the Bacillus subtilis against the Cnaphalocrocis medinalis Guenée (Lepidoptera: Crambidae). (2nd January 2023) - Ramasubramanian, Ramakrishnan; Karthi, Sengodan; Senthil-Nathan, Sengottayan; Sivanesh, Haridoss; Shyam Sundar, Narayanan; Stanley-Raja, Vethamonickam; Ramkumar, Govindaraju; Chanthini, Kanagaraj Muthu-Pandian; Vasantha-Srinivasan, Prabhakaran; Alarjani, Khaloud Mohammed; Elshikh, Mohamed S; Abdel-Megeed, Ahmed; et al.
Abstract: In recent times, controlling agricultural diseases and pests using chemical pesticides is broadly applied and is considered effective but it is not considered as eco-friendly. For pest control, biological ways have been considered sustainable and safe. As bio-control agents, the Bacillus species exhibit a large spectrum of biological activity. The application of Bacillus subtilis as a potential bio-control agent against the lepidopteran pest, the rice leaffolder, Cnaphalocrocis medinalis is the focus of our study. The strain B. subtilis -MW365355 was identified by morphological, biochemical, and genetic analyses. Under laboratory conditions, cell suspensions of B. subtilis (Bs) were added to an artificial diet, fed to C. medinalis and the effects of the bacterial ingestion were evaluated by measuring the feeding, growth, food utilization and behavioral response of C. medinalis . An effect of B. subtilis in the artificial diet was evaluated with the different spore concentrations of 3.2 × 10 5, 6.3 × 10 5, 1.5 × 10 7 and 4.1 × 10 7 CFU/ml. The larvae fed with the B. subtilis amended diet had a significantly reduced growth efficiency compared to the control group fed with a bacteria-free diet. In conclusion of our study, B. subtilis (Bs) will significantly contribute to the management of leaffolder disease in the future.